Becoming a winner a workbook for values education, personality development and character building - Roldan, Amelia Samson; Santos, Marian Joyce Roldan (AR Skills Development & Management Services, 2016)
"This book can be used by schools in their personality development programs or by non-government organizations involved in human formation. It can also be used by individuals who are still searching...for their identity, inner peace, happiness, success in their studies or career, and for a formula for overcoming the challenges and difficulties of day-to-day living."--Preface